Análisis de la Cooperación Internacional en el departamento del Valle del Cauca en los periodos comprendidos entre 2018-2021 (2023)
This monograph aims to analyze the characteristics of international cooperation in the department of Valle del Cauca between the periods 2018-2021 in order to know what were the key entities involved in the process of international cooperation and identify what strategies are sought to raise the efficiency and strengthening of the resources delivered by donors to the region; Through the different types of cooperation that exist, this study was achieved by collecting secondary information from documents of government entities, academic publications and records of multilateral organizations, taking into account a series of principles, concepts and theories that guide the actions and strategies to be carried out in this research.